Answer:
![\rm\displaystyle 0,\pm\pi](https://tex.z-dn.net/?f=%5Crm%5Cdisplaystyle%20%200%2C%5Cpm%5Cpi%20%20)
Step-by-step explanation:
please note that to find but α+β+γ in other words the sum of α,β and γ not α,β and γ individually so it's not an equation
===========================
we want to find all possible values of α+β+γ when <u>tanα+tanβ+tanγ = tanαtanβtanγ</u><u> </u>to do so we can use algebra and trigonometric skills first
cancel tanγ from both sides which yields:
![\rm\displaystyle \tan( \alpha ) + \tan( \beta ) = \tan( \alpha ) \tan( \beta ) \tan( \gamma ) - \tan( \gamma )](https://tex.z-dn.net/?f=%20%20%5Crm%5Cdisplaystyle%20%20%5Ctan%28%20%5Calpha%20%29%20%20%2B%20%20%5Ctan%28%20%5Cbeta%20%29%20%3D%20%20%5Ctan%28%20%5Calpha%20%29%20%20%5Ctan%28%20%5Cbeta%20%29%20%20%5Ctan%28%20%5Cgamma%20%29%20%20-%20%20%5Ctan%28%20%5Cgamma%20%29%20)
factor out tanγ:
![\rm\displaystyle \tan( \alpha ) + \tan( \beta ) = \tan( \gamma ) (\tan( \alpha ) \tan( \beta ) - 1)](https://tex.z-dn.net/?f=%5Crm%5Cdisplaystyle%20%20%5Ctan%28%20%5Calpha%20%29%20%20%2B%20%20%5Ctan%28%20%5Cbeta%20%29%20%3D%20%20%20%5Ctan%28%20%5Cgamma%20%29%20%28%5Ctan%28%20%5Calpha%20%29%20%20%5Ctan%28%20%5Cbeta%20%29%20-%20%201%29)
divide both sides by tanαtanβ-1 and that yields:
![\rm\displaystyle \tan( \gamma ) = \frac{ \tan( \alpha ) + \tan( \beta ) }{ \tan( \alpha ) \tan( \beta ) - 1}](https://tex.z-dn.net/?f=%5Crm%5Cdisplaystyle%20%20%20%5Ctan%28%20%5Cgamma%20%29%20%3D%20%20%5Cfrac%7B%20%5Ctan%28%20%5Calpha%20%29%20%20%2B%20%20%5Ctan%28%20%5Cbeta%20%29%20%7D%7B%20%5Ctan%28%20%5Calpha%20%29%20%20%5Ctan%28%20%5Cbeta%20%29%20%20%20%20-%201%7D)
multiply both numerator and denominator by-1 which yields:
![\rm\displaystyle \tan( \gamma ) = - \bigg(\frac{ \tan( \alpha ) + \tan( \beta ) }{ 1 - \tan( \alpha ) \tan( \beta ) } \bigg)](https://tex.z-dn.net/?f=%5Crm%5Cdisplaystyle%20%20%20%5Ctan%28%20%5Cgamma%20%29%20%3D%20%20%20-%20%20%5Cbigg%28%5Cfrac%7B%20%5Ctan%28%20%5Calpha%20%29%20%20%2B%20%20%5Ctan%28%20%5Cbeta%20%29%20%7D%7B%201%20-%20%5Ctan%28%20%5Calpha%20%29%20%20%5Ctan%28%20%5Cbeta%20%29%20%20%20%7D%20%5Cbigg%29)
recall angle sum indentity of tan:
![\rm\displaystyle \tan( \gamma ) = - \tan( \alpha + \beta )](https://tex.z-dn.net/?f=%5Crm%5Cdisplaystyle%20%20%20%5Ctan%28%20%5Cgamma%20%29%20%3D%20%20%20-%20%20%5Ctan%28%20%5Calpha%20%20%2B%20%20%5Cbeta%20%29%20)
let α+β be t and transform:
![\rm\displaystyle \tan( \gamma ) = - \tan( t)](https://tex.z-dn.net/?f=%5Crm%5Cdisplaystyle%20%20%20%5Ctan%28%20%5Cgamma%20%29%20%3D%20%20%20-%20%20%5Ctan%28%20t%29%20)
remember that tan(t)=tan(t±kπ) so
![\rm\displaystyle \tan( \gamma ) = -\tan( \alpha +\beta\pm k\pi )](https://tex.z-dn.net/?f=%5Crm%5Cdisplaystyle%20%20%20%5Ctan%28%20%5Cgamma%20%29%20%3D%20%20%20%20-%5Ctan%28%20%20%20%5Calpha%20%20%20%2B%5Cbeta%5Cpm%20k%5Cpi%20%29%20)
therefore <u>when</u><u> </u><u>k </u><u>is </u><u>1</u> we obtain:
![\rm\displaystyle \tan( \gamma ) = -\tan( \alpha +\beta\pm \pi )](https://tex.z-dn.net/?f=%5Crm%5Cdisplaystyle%20%20%20%5Ctan%28%20%5Cgamma%20%29%20%3D%20%20%20%20-%5Ctan%28%20%20%20%5Calpha%20%20%20%2B%5Cbeta%5Cpm%20%5Cpi%20%29%20)
remember Opposite Angle identity of tan function i.e -tan(x)=tan(-x) thus
![\rm\displaystyle \tan( \gamma ) = \tan( -\alpha -\beta\pm \pi )](https://tex.z-dn.net/?f=%5Crm%5Cdisplaystyle%20%20%20%5Ctan%28%20%5Cgamma%20%29%20%3D%20%20%20%20%5Ctan%28%20%20%20-%5Calpha%20%20-%5Cbeta%5Cpm%20%5Cpi%20%29%20)
recall that if we have common trigonometric function in both sides then the angle must equal which yields:
![\rm\displaystyle \gamma = - \alpha - \beta \pm \pi](https://tex.z-dn.net/?f=%5Crm%5Cdisplaystyle%20%20%5Cgamma%20%20%3D%20%20%20%20%20%20-%20%20%20%5Calpha%20%20%20-%20%20%5Cbeta%20%5Cpm%20%5Cpi%20)
isolate -α-β to left hand side and change its sign:
![\rm\displaystyle \alpha + \beta + \gamma = \boxed{ \pm \pi }](https://tex.z-dn.net/?f=%5Crm%5Cdisplaystyle%20%5Calpha%20%20%2B%20%20%5Cbeta%20%20%2B%20%20%20%5Cgamma%20%20%3D%20%20%5Cboxed%7B%20%5Cpm%20%5Cpi%20%20%7D)
<u>when</u><u> </u><u>i</u><u>s</u><u> </u><u>0</u>:
![\rm\displaystyle \tan( \gamma ) = -\tan( \alpha +\beta \pm 0 )](https://tex.z-dn.net/?f=%5Crm%5Cdisplaystyle%20%20%20%5Ctan%28%20%5Cgamma%20%29%20%3D%20%20%20%20-%5Ctan%28%20%20%20%5Calpha%20%20%20%2B%5Cbeta%20%5Cpm%200%20%29%20)
likewise by Opposite Angle Identity we obtain:
![\rm\displaystyle \tan( \gamma ) = \tan( -\alpha -\beta\pm 0 )](https://tex.z-dn.net/?f=%5Crm%5Cdisplaystyle%20%20%20%5Ctan%28%20%5Cgamma%20%29%20%3D%20%20%20%20%5Ctan%28%20%20%20-%5Calpha%20%20%20-%5Cbeta%5Cpm%200%20%29%20)
recall that if we have common trigonometric function in both sides then the angle must equal therefore:
![\rm\displaystyle \gamma = - \alpha - \beta \pm 0](https://tex.z-dn.net/?f=%5Crm%5Cdisplaystyle%20%20%5Cgamma%20%20%3D%20%20%20%20%20%20-%20%20%20%5Calpha%20%20%20-%20%20%5Cbeta%20%5Cpm%200%20)
isolate -α-β to left hand side and change its sign:
![\rm\displaystyle \alpha + \beta + \gamma = \boxed{ 0 }](https://tex.z-dn.net/?f=%5Crm%5Cdisplaystyle%20%5Calpha%20%20%2B%20%20%5Cbeta%20%20%2B%20%20%20%5Cgamma%20%20%3D%20%20%5Cboxed%7B%200%20%20%7D)
and we're done!